Gene Polymorphisms of m6A Erasers FTO and ALKBH1 Associated with Susceptibility to Gastric Cancer - Li Y; Zhou D; Liu Q; Zhu W; Ye Z; He C (Dove Medical Press, 2022)
Yue Li,* Dalei Zhou,* Qing Liu, Weijie Zhu, Zulu Ye, Caiyun He Department of Molecular Diagnostics, Sun Yat-Sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangzhou, 510060, People's Republic of China*These authors contributed equally to this workCorrespondence: Caiyun He; Zulu Ye, Department of Molecular Diagnostics, Sun Yat-Sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, No. 651, Dongfeng Road, Yuexiu District, Guangzhou, 510060, People's Republic of China, Tel +86-18665593050 ; +86-15017590433, Fax +20-87340921, Email hecy@sysucc.org.cn; yezl@sysucc.org.cnPurpose: Fat mass and obesity-associated protein (FTO) and AlkB homolog 1 (ALKBH1) are m6A demethylases that have been demonstrated to be associated with the overall survival of patients with gastric cancer (GC). This study investigates the influence of genetic variants of FTO and ALKBH1 on susceptibility to GC.Patients and Methods: Potentially functional single nucleotide polymorphisms (SNPs) of FTO and ALKBH1 were genotyped in 419 patients with GC and 569 healthy controls by Kompetitive allele-specific PCR.Results: The AG and AG/AA variants of FTO rs2287142 were significantly associated with a decreased GC risk (for AG/AA vs GG: adjusted OR = 0.73, p = 0.020). The GA and GA/GG variants of ALKBH1 rs1076496 were closely correlated with an increased risk of GC in people aged ≥ 55 years (for GA/GG vs AA: adjusted OR = 1.51, p = 0.041) but showed a decreasing tendency of risk of GC in people aged < 55 years (adjusted OR = 0.85, p = 0.444). FTO rs2287142 and ALKBH1 rs1076496 conformed to the principle of a dominant model. FTO haplotype rs1421091-rs1421092-rs2287142-rs9939609 CTAT was closely associated with a lower risk of total GC (adjusted OR = 0.62, p = 0.023), while CTGA was linked with an increased risk of intestinal GC (adjusted OR = 2.51, p = 0.005). ALKBH1 rs1048147-rs1076496-rs11159286 CAC haplotype was significantly associated with a decreased risk of GC in people aged ≥ 55 years (adjusted OR = 0.41, p = 0.008). The FTO rs2287142-rs9939609 AG/AA-TT combination was associated with a decreased risk of GC only in the presence of rs1421091 TC/TT (adjusted OR = 0.70, p = 0.047), demonstrating that these FTO SNPs might have a cooperative effect on susceptibility to GC.Conclusion: FTO and ALKBH1 SNPs may have predictive value in evaluating susceptibility to GC with differing age or Lauren classification.Keywords: FTO, ALKBH1, gastric cancer, susceptibility, Lauren classification